Pathological perspective reveals a novel hemodialyzer reaction: a case report - Weijuan Lou; Yongchun Xi; Ya Liu; Xueling Cai; Junfang Gai; Jianyong Yin; Jiahui Ding; Yifang Yang; Yanjuan Teng; Tingfang Chen; Niansong Wang; Yongping Guo (BMC Nephrology)
Abstract Background While the appearance of red clots in the dialyzer and the arterial and venous blood tubing lines is a common phenomenon in every hemodialysis unit, the occurrence of recurrent yellowish-white matter formation in the hemodialysis venous blood pot of a patient is rare. Case presentation We describe a male 69-year-old male with recurrent yellowish-white matter formation in the hemodialysis venous blood pot and red clots in the dialyzer. This was associated with a significant decrease in his red blood cells count. He had no history of thrombus no pro-thrombotic risk factors could be identified. Light microscopic examination of the deposits revealed the presence of large aggregates of neutrophils, large amounts of fibrin. The yellowish-white matter recurred at the next dialysis session. The occurrence of this episode was completely resolved by switching the dialysis filter and could not be avoided by increasing low molecular weight heparin dosage. Conclusion The yellowish-white matter and clotting within the dialyzer, as well as severe anemia, could be prevented by changing the type of dialyzer. Due to the rarity of this dialyzer reaction, it is important that awareness of this reaction by early identification be undertaken.